Vulnerabilidade à erosão costeira no município de Baía da Traição – Paraíba, Brasil - Araujo, Diandra Soares de (2023)
Baía da Traição is a municipality in Paraíba located in the Intermediate Geographic Region of João Pessoa and in the Immediate Geographic Region of Mamanguape - Rio Tinto, and its eastern portion is bathed by the Atlantic Ocean. However, the unrestrained and unorganized occupation of the coastal plain of the municipality, added to natural factors, are the elements responsible for the erosion that affects the coastal zone of the municipality, making it a vulnerable environment. Several methodologies have been used to assess the coastal vulnerability of beaches worldwide, including geoindicators. Considering the absence of studies on this subject, this research aims to identify vulnerability to coastal erosion in the municipality of Baía da Traição through physical and anthropogenic geoindicators. For this, it was necessary to carry out some methodological procedures, namely: bibliographic survey, secondary data collection, field activities, and the use of GIS (Geographic Information System) tools, through the analysis of the evolution of the coastline of the municipality object of this study and treatment of the results in a GIS environment. To define the degree of vulnerability to coastal erosion of Baía da Traição, an adaptation of the methodology proposed by Sousa et al. (2011); Menezes et al. (2018); and Bush et al. (1999) were carried out. Thus, 29 points distributed along the edge of the municipality were defined, 500 meters apart, and some geoindicators were analyzed, such as the morphology of the beach, the presence of dunes and vegetation fields, the position of the coastline (through the CASSIE tool, short for Coastal Analyst System From Space Imagery Engine), among others. Each geoindicator was classified according to its potential for coastal vulnerability, which, after carrying out the research stages, could be defined as high, moderate, or low. After carrying out all stages of the research, it was possible to obtain the current panorama of the vulnerability to erosion to which the coastal zone of Baía da Traição is subject. Thus, the research showed that 56.36% of the extension of the coastal zone of the municipality studied is in moderate vulnerability, 26.80% is in low vulnerability, and 16.82% is in high vulnerability. It was possible to verify that the areas of higher occupational density coincide with those of greater vulnerability. On the other hand, some factors were decisive in making some beaches less vulnerable, such as the presence of dunes, beach rocks in some areas, vegetation, and the absence of buildings on the beach. Through the study, it was possible to understand that public agencies must develop projects to monitor the situation of areas of medium and high vulnerability to coastal erosion in Baía da Traição. Although some adaptation strategies used in Brazil and the world to contain the effects of coastal erosion are presented in the work, none of these measures should be taken without discussion with the academic community and the local community, as all of them may have negative consequences, including the intensification of the problem.